3-Dimensional coculture of breast cancer cell lines with adipose tissue–Derived stem cells reveals the efficiency of oncolytic Newcastle disease virus infection via labeling technology - Salman, Marwa Ibrahim; Al-Shammari, Ahmed Majeed; Emran, Mahfodha Abbas (Frontiers in Molecular Biosciences, 2022)
Oncolytic virotherapy is one of the emerging biological therapeutics that needs a more efficient in vitro tumor model to overcome the two-dimensional (2D) monolayer tumor cell culture model's inability to maintain the tissue-specific structure. This is to offer significant prognostic preclinical assessment findings. One of the best models that can mimic the in vivo model in vitro is three-dimensional (3D) tumor-normal cell co-culture systems which can be employed in preclinical oncolytic viruses' therapeutics. Thus, we developed our 3-dimensional co-culture system in vitro using two types of breast cancer cell lines showing different receptors statuses co-cultured with adipose tissue-derived mesenchymal stem cells. The cells were cultured in a floater tissue culture plate to allow spheroids formation, and then spheroids were collected and transferred to a scaffold spheroids dish. These 3D culture systems were used to evaluate oncolytic Newcastle disease virus AMHA1 strain infectivity and antitumor activity using a tracking system of NDV labeled with fluorescent PKH67 linker to follow viral entrance into target cells. This provides evidence indicating that NDV AMHA1 strain is an efficient oncolytic agent. The fluorescently detected virus particles showed high intensity in both co-culture spheres. Strategies for chemically introducing fluorescent dye into NDV particles extract quantitative information from infected cancer models. In conclusion, the results indicate that the NDV AMHA1 strain efficiently replicates and induces an antitumor effect in cancer-normal 3D co-culture systems, indicating efficient clinical outcomes.